Lung Deposition Using the Respimat® Soft Mist™ Inhaler Mono and Fixed-Dose Combination Therapies: An In Vitro/In Silico Analysis. (23rd November 2020) - Ciciliani, Anna-Maria; Denny, Mark; Langguth, Peter; Voshaar, Thomas; Wachtel, Herbert
Abstract: Tiotropium and olodaterol are mainstay treatments for chronic obstructive pulmonary disease (COPD) and yield important clinical improvements, especially when used in fixed-dose combination. Whilst previous studies have shown consistent delivery of tiotropium to the lungs with the Respimat ® inhaler, no such study has been carried out for olodaterol or the components of their fixed-dose combination (TIO/OLO). Combining in vitro and in silico models, we measured the amount of drug retained in the mouth–throat area, entering the trachea and reaching the lung periphery. We applied a hybrid deposition model that considered the experimentally determined output of an Alberta throat model ( in vitro – dose to lung) combined with a computational fluid dynamic model of the lungs ( in silico ). Regardless of the COPD breathing pattern, ≥50% of the nominal dose of either tiotropium, olodaterol, or TIO and OLO in the fixed-dose combination reached the lung. Of the dose reaching the lungs, greater than 50% is deposited in the lung periphery (from generation 8 onwards). Our study demonstrated that aerosol delivery via the Respimat inhaler achieved high deposition deep into the lung periphery with all formulations evaluated.